Transformation and upgrading path for midstream manufacturers in the chain: Taking Shennan Circuits as an example - You, Lei; Yang, Meiying (Frontiers in Environmental Science, 2022)
The restructuring of global value chain restructuring has created both opportunities and challenges for Chinese manufacturers. In the process, OEM-ODM-OBM has been a typical upgrade path for manufacturing enterprises to integrate into the global value chain. However, this path may not be appropriate for Chinese midstream enterprises in the industry chain. This paper performs a longitudinal analysis of 30-year reform of Shennan Circuits, a typical midstream manufacturing business in the industry chain in China. Based on the smiling curve theory, we systematically analyzed how Shennan Circuit constantly scanned over the industry, its customers, competitors, and leveraged its own capability and resources against the background of global value chain restructuring to successfully integrate into the global value chain, enhance competitiveness while completing business transformation and upgrade. Given the case study, this paper proposes three types of transformation solutions with eight specific paths and the ICCA opportunity scanning analysis method for China's midstream manufacturers in the industry chain as references.